ANALYSIS OF THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS (SAK EMKM) IN SCARVEIL MSME FINANCIAL REPORTS - Meilani, Melan Nur; Drajat, Alvira Zulfa; Andaresta, Tita; Prayoga, Muhammad Adam Khayla; Armayza, M. Adnan; Kurniati, Fitrina (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2025)
This study aims to analyze the impact of implementing the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) on the financial performance of Scarveil and provide recommendations for improving the quality of financial reports. A descriptive qualitative approach was used, involving interviews, observations, and documentation. Data collected includes financial reports and transaction records from Scarveil. The analysis indicates that although some accounting practices are adequate, further improvement in compliance with accounting standards is essential for enhancing profitability and business sustainability. This study focuses solely on Scarveil, so the findings may not be generalizable to all SMEs in Indonesia. The study contributes to a deeper understanding of the importance of SAK EMKM implementation for MSMEs in Indonesia, helping business practitioners and policymakers improve financial report transparency and accountability, offering new insights into the relationship between accounting standards and financial success in this sector.